Muaddib develop muaddab: Integration of Rasulullah's method in UDL to produce human being in teaching and learning literacy - NorHamidah Ibrahim; Mohd. Hanafi Mohd; Noraidah Sahari @ Ashaari; Ahmad Syukry Ibrahim; Mohd Saleh Abbas; Habibah Artini Ramlie; Mohd Norazmi Nordin (ASR Research India, 2022)
This concept paper is written to see the importance of including the Rasulullah Method as muaddib to develop muaddab and then form balance human being in the practice of teaching and learning literacy based on Universal Design for Learning (UDL). The goal of UDL is to make learning accessible and challenging for all. UDL is founded on three basic principles: Representation, Engagement and Action and Expression. UDL is an important method of reducing barriers to teaching and learning in remedial classrooms. The integration of Rasulullah and UDL Method is proposed to be implemented more systematically through the study of teaching and learning model design based on expert perspective.